Numerical Simulation of Surface Dielectric Barrier Discharge With Functionally Graded Material - Zhang, Zelin (Frontiers in Physics, 2022)
Atmospheric-pressure surface dielectric barrier discharge (SDBD) has drawn significant attention, and the influence on the SDBD characteristics of surface dielectric barrier materials has been widely studied. In this work, a two-dimensional self-consistent fluid model is built to investigate the effect of barrier material characteristics on SDBD, by introducing a linear permittivity distribution. It is demonstrated that a dielectric barrier with gradient permittivity can affect the SDBD by changing the electric field distribution near the surface and speeding up the propagation of the streamer. The gradient permittivity along the layer of the dielectric barrier plays a significant role in improving the dynamic characteristics of the SDBD.